Atomically ordered Pt3Mn intermetallic electrocatalysts for the oxygen reduction reaction in fuel cells. Issue 13 (7th March 2022) - Lim, Jeonghoon; Jung, Chanwon; Hong, Doosun; Bak, Junu; Shin, Jaewook; Kim, MinJoong; Song, DongHoon; Lee, Changsoo; Lim, Jinkyu; Lee, Hyunjoo; Lee, Hyuck Mo; Cho, EunAe
Abstract : A Pt3 Mn intermetallic ORR electrocatalyst was synthesized using a facile synthesis without using additional multi-steps, and exhibits superior single-cell performance and durability. Abstract : Here, we introduce structurally ordered platinum–manganese nanoparticles on a carbon support (Pt3 Mn intermetallic/C) as a highly efficient and durable catalyst for the oxygen reduction reaction (ORR). Using a facile method, Pt3 Mn intermetallic nanoparticles were obtained without severe agglomeration. Compared to commercial Pt/C, Pt3 Mn intermetallic/C demonstrates superior initial ORR activity and stability. DFT calculations demonstrated highly active and stable Pt3 Mn by calculations of the oxygen adsorption energy, segregation energy, and Pt dissolution potential. One of the main challenges in the commercialization of new ORR catalysts is the successful transition from a rotating disk electrode to a single cell. At a cell voltage of 0.7 V, Pt3 Mn intermetallic/C (550 → 486 mA cm −2, −11.63%) showed excellent initial cell performance and stability after 10k voltage cycles compared to Pt/C (419 → 308 mA cm −2, −26.49%). We report for the first time a Pt3 Mn intermetallic ORR catalyst that achieves single-cell performance superior to that of Pt/C.